Pengaruh Perencanaan Pajak Dan Return On Assets Terhadap Nilai Perusahaan Dengan Likuiditas Sebagai Variabel Intervening Pada Perusahaan Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa - Zara Hayati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the effect of Tax Planning and Return on Assets on Firm Value with Liquidity as an intervening variable in Transportation and Logistics sector companies listed on the Indonesia Stock Exchange in 2020-2024. The population in this study uses transportation and logistics companies listed on the Indonesia Stock Exchange in 2020-2024 with the Purpose Sampling method. The analytical method in this study is panel data regression analysis. The results show that Tax Planning partially has no significant effect on liquidity, Return on Assets partially has no significant effect on liquidity, Tax Planning partially has a positive and significant effect on firm value, Return on Assets partially has a negative and significant effect on Firm Value, Liquidity partially has a positive and significant effect on Firm Value, Liquidity does not mediate the effect of tax planning on firm value, liquidity mediates the effect of return on assets on firm value.